Pengaruh Pemberian Aromaterapi Minyak Atsiri Bunga Tembakau terhadap Penurunan Tingkat Stres pada Lansia di Dinas Sosial UPT Pelayanan Sosial Tresna Werdha Bondowoso - Pratidina, Amanda Virga; Nugroho, Setiyo Adi; Hafifah, Vivin Nur (Universitas Pahlawan Tuanku Tambusai, 2024)
Elderly people living in nursing homes often experience mental disorders such as stress. Stress is a condition where there is an imbalance between the demands and abilities of the individual which causes reactions to psychological and physical disorders. Everyone will experience stress in their lives because of a stimulus that initiates or triggers a change called a stressor. One alternative that can be used to reduce stress levels is by giving aromatherapy. This pre-experimental study with a one-group pre-post test design aims to determine the effect of tobacco flower essential oil aromatherapy on reducing stress levels in the elderly at the Dinas Sosial UPT Pelayanan Sosial Tresna Werdha Bondowoso. 45 respondents were selected based on the research criteria with simple random sampling technique. The Wilcoxon Signed Rank test was used in data analysis and obtained a p value of 0.000 <0.05 which means that there is an effect of giving tobacco flower essential oil aromatherapy on reducing stress levels in the elderly at the Dinas Sosial UPT Pelayanan Sosial Tresna Werdha Bondowoso.